ANALISIS PENDAPATAN USAHATANI TOMAT DI DESA TONSEWER KECAMATAN TOMPASO KABUPATEN MINAHASA - Celcius Talumingan (AGRI-SOSIOEKONOMI, 2011)
This study aims to determine the costs and farm income. Research carried on in March to May 2010 in the village of Tonsewer, district of Tompaso, Regency of Minahasa. The data obtained in this study include primary data and secondary data. The method of collecting data was obtained by interview using the questionnaire as a tool in data collection. Primary data were obtained from tomato farmers and secondary data obtained from the relevant authorities of this research. Results showed that most farmers in the village of respondents aged   28-67 years, having elementary through high school levels, the number of dependents a family of 3 to 4 people and is the owner of tenant farmers. This study uses the income analysis to determine the level of income from tomato farmers and comparative analysis between revenue and costs  to determine the level of success of farming tomatoes. The results showed that the average farmer's income of Rp 3,386,987.8 per two planting seasons or Rp 4,908,784.6 per one planting season.  R/C  > 1 is a successful farmer in tomato farming.